the EDUCATION AND ANTICIPATION USING RELATED TO THE COVID-19 PLACE FOR THE COMMUNITY OF TAROGONG VILLAGE, KECAMATAN TAROGONG KIDUL, KABUPATEN GARUT, JAWA BARAT - Novi Yanti (Indonesian Journal of Community Empowerment (IJCE), 2020)
This time, this community service aims to anticipate and educate the public regarding the COVID-19 outbreak which is currently attacking the entire world. The method used is in the form of counseling and data collection of people affected and not affected by the COVID-19 outbreak. Programs that are carried out online as well as giving PPE directly. Data collection is carried out by discussing the village head and staff in the village. The target of this service is the Tarogong Village Community, Tarogong Kidul District, Garut Regency, West Java. The result of this service, the community understands and understands what to pay attention to to overcome the COVID-19 outbreak and how to anticipate the COVID-19 outbreak.